Sensitive and precise visually guided drug delivery nanoplatform with dual activation of pH and light. (15th March 2022) - Liu, Chenyu; Zhou, Hengjun; Yu, Simiao; Chen, Hailiang; Wang, Ning; Yao, Weihe; Lu, An-Hui; Qiao, Weihong
Abstract: Controlled-release drug carriers in cancer therapy are the most ideal way to reduce toxicity and improve drug efficacy. Since light stimulation is precise and operable, most multi-stimulation response carriers utilize phototherapy to enhance release efficiency. However, phototoxicity severely limits the application of phototherapy. Herein, we designed and synthesized a Cou-ONB lipid with sensitive fluorescence feedback and multi-stimulus response. COBL liposomes prepared from Cou-ONB lipids will passively aggregate at the tumor and guide phototherapy by fluorescence. More importantly, it can reflect the drug release effect in vivo through its own sensitive fluorescence changes, further enabling precise phototherapy and reducing phototoxicity. In this paper, the multi-stimulus superimposed response and precise fluorescence-guided performance of COBL liposomes were investigated at the molecular, liposome, cellular, and animal levels. Finally, tumor treatment experiments showed that the d -COBL-UV group had the best tumor suppression effect (5.3-fold). This paper highlights a real-time fluorescence-guided multi-stimulus superposition strategy and provides a design idea to precisely implement exogenous stimuli by displaying the degree of drug release, aiming to achieve less toxic and more efficient cancer therapy through timely and precise multi-stimulation. Statement of significance: Multi-stimulus responsive drug carriers have been extensively developed in the last decade. Visual guidance is an important tool to achieve precision medicine and precise control of drug release. However, the available visualization materials are more aimed at directing stimulation at the optimal moment. There is little discussion on when to stop exogenous stimulation and how to minimize the damage of stimulation to the patient. Here, we provide a Cou-ONB lipid that not only responds to multiple stimuli, but also provides sensitive feedback on its own dissociation with a fluorescent signal so that physicians can adjust exogenous stimuli in a timely manner. This paper provides insights to facilitate precision drug delivery systems, providing viable design ideas for precise, efficient, and less toxic cancer therapies. Graphical abstract: Image, graphical abstract